2022
DOI: 10.3389/fclim.2022.844831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Current and Future Summer Marine Heat Waves on Posidonia oceanica: Plant Origin Matters?

Abstract: Marine heat waves (MHWs), prolonged discrete anomalously warm water events, have been increasing significantly in duration, intensity and frequency all over the world, and have been associated with a variety of impacts including alteration of ecosystem structure and function. This study assessed the effects of current and future MHWs on the Mediterranean seagrass Posidonia oceanica performance, also testing the importance of the thermal environment where the plant lives. The effects of current MHWs were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 86 publications
(105 reference statements)
2
10
0
Order By: Relevance
“…3 m of depth) were similar at the three study sites, with a clear increase in T 1 (after 3 weeks from the initial plume injection) and a partial recovery in T 2 (after 11 weeks; Figure S1A). The simulated MHWs resembled either current or future scenarios according to Hobday et al [3]: the magnitude of the two T anomalies corresponded to conditions observed in the study area during the 2000-2009 decade (+1.4-1.8 • C) and those expected in the future under the worst prediction scenarios (+4.5-5.1 • C) [29] (Figure S1B).…”
Section: Study Area and Sampling Strategysupporting
confidence: 59%
See 2 more Smart Citations
“…3 m of depth) were similar at the three study sites, with a clear increase in T 1 (after 3 weeks from the initial plume injection) and a partial recovery in T 2 (after 11 weeks; Figure S1A). The simulated MHWs resembled either current or future scenarios according to Hobday et al [3]: the magnitude of the two T anomalies corresponded to conditions observed in the study area during the 2000-2009 decade (+1.4-1.8 • C) and those expected in the future under the worst prediction scenarios (+4.5-5.1 • C) [29] (Figure S1B).…”
Section: Study Area and Sampling Strategysupporting
confidence: 59%
“…This creates a marked seawater temperature gradient in the vicinity of the discharge point which is conceivably moderated by season and weather conditions. The historical occurrence, duration, and intensity of MHWs occurring in the last 20 years in the study area have been characterized previously [29]. To run our experiment, we profited from ca.…”
Section: Study Area and Sampling Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This indication converges with evidence gained from other seagrass species (Pagès et al, 2010;Llagostera et al, 2016), whereby leaf necrosis is considered as an indicator of irreversible heat-induced damage of the leaf tissue (Beca-Carretero et al, 2020). However, further research is necessary to question to what extent the necrosis should be seen as a sign of leaf senescence or a manifestation of the activation of a process that could improve the survival of the plant, as a higher percentage of necrosis was found after the MHWs in P. oceanica shoots from warmer sites compared to those from colder sites (Stipcich et al, 2022). Overall, shoot density of P. oceanica meadows at the study sites was found to influence morphological traits.…”
Section: Discussionmentioning
confidence: 99%
“…An important shoot mortality of P. oceanica was estimated in meadows during [2002][2003][2004][2005][2006] where two intense MHWs occurred in Spain (Marbà and Duarte, 2010). Depending on the temperature intensity and heat duration, MHWs can also have sublethal morphological effects on both P. oceanica cuttings (Stipcich et al, 2022) and seedlings (Guerrero-Meseguer et al, 2017), by inducing leaf loss, reducing leaf growth, and triggering leaf necrosis. Seagrasses may be highly susceptible to sudden warming events (Chefaoui et al, 2018) and a functional extinction of P. oceanica by the middle of this century has been hypothesized (Jordà et al, 2012).…”
Section: Introductionmentioning
confidence: 99%